Overexpression of AtABCG25 enhances the abscisic acid signal in guard cells and improves plant water use efficiency. (October 2016) - Kuromori, Takashi; Fujita, Miki; Urano, Kaoru; Tanabata, Takanari; Sugimoto, Eriko; Shinozaki, Kazuo
Highlights: AtABCG25 was previously identified as an ABA transmembrane transporter. AtABCG25 -overexpressing plants showed a reduced-transpiration phenotype. Overexpression of AtABCG25 enhanced the ABA signal in guard cells. AtABCG25 overexpression improved drought tolerance without any growth retardation. AtABCG25 overexpression improved the water use efficiency of plants. Abstract: In addition to improving drought tolerance, improvement of water use efficiency is a major challenge in plant physiology. Due to their trade-off relationships, it is generally considered that achieving stress tolerance is incompatible with maintaining stable growth. Abscisic acid (ABA) is a key phytohormone that regulates the balance between intrinsic growth and environmental responses. Previously, we identified AtABCG25 as a cell-membrane ABA transporter that export ABA from the inside to the outside of cells. AtABCG25 -overexpressing plants showed a lower transpiration phenotype without any growth retardation. Here, we dissected this useful trait using precise phenotyping approaches. AtABCG25 overexpression stimulated a local ABA response in guard cells. Furthermore, AtABCG25 overexpression enhanced drought tolerance, probably resulting from maintenance of water contents over the common threshold for survival after drought stress treatment. Finally, we observed enhanced water use efficiency by overexpression of AtABCG25, in addition to drought tolerance. These results were consistent with the function of AtABCG25 as an ABA efflux transporter. This unique trait may be generally useful for improving the water use efficiency and drought tolerance of plants.